Developing a Supportive Community of Practice: A Doctoral Case Study - Jones, Jan; Ward, Mervyn; Szubryt, Patrycjusz; Franzen-Waschke, Ute; Rowe, Lisa (GILE Journal of Skills Development, 2024)
This paper employs a qualitative case study to suggest how the research journey of doctoral students can be improved in educational institutions by encouraging the formation of small and informal Communities of Practice (CoP). It examines themes emerging from the feelings and opinions of four part-time professional doctorate students about their study experience and participation in their emergent CoP. A peer group developed where the students share their experience, expertise, insight, and knowledge in a caring and supportive, but informal, forum. CoP could become an effective tool to aid retention, identity development and wellbeing of postgraduate level students, factors which have been previously identified as key areas of risk. An autoethnographic approach was used to review the feelings, perceptions, and opinions of the four case study group members about their experiences of the informal CoP to date. Thematic analysis of transcripts and WhatsApp communications was used to reveal the perceived common benefits and gains from participation in the informal CoP such as joy, safe spaces, and identity development, aligning members experiences to a CoP lifecycle. The study found small group formation at doctoral programme induction, and encouragement for students to organise their own regular study days using of social channels, may impact overall success. Application and adaptation of this doctoral CoP model could form the basis for future research and a model for academic institutions to suggest to new and existing students